Digestibility of wheat alpha-amylase/trypsin inhibitors using a caricain digestive supplement - Juhász, Angéla; Nye-Wood, Mitchell G.; Tanner, Gregory J.; Colgrave, Michelle L. (Frontiers in Nutrition, 2022)
Wheat is a major source of nutrition, though in susceptible people it can elicit inappropriate immune responses. Wheat allergy and non-celiac wheat sensitivity are caused by various wheat proteins, including alpha-amylase trypsin inhibitors (ATIs). These proteins, like the gluten proteins which can cause celiac disease, are incompletely digested in the stomach such that immunogenic epitopes reach the lower digestive system where they elicit the undesirable immune response. The only completely effective treatment for these immune reactions is to eliminate the food trigger from the diet, though inadvertent or accidental consumption can still cause debilitating symptoms in susceptible people. One approach used is to prevent the causal proteins from provoking an immune reaction by enhancing their digestion using digestive protease supplements that act in the stomach or intestine, cleaving them to prevent or quench the harmful immune response. In this study, a digestive supplement enriched in caricain, an enzyme naturally present in papaya latex originally designed to act against gluten proteins was assessed for its ability to digest wheat ATIs. The digestion efficiency was quantitatively measured using liquid chromatography-mass spectrometry, including examination of the cleavage sites and the peptide products. The peptide products were measured across a digestion time course under conditions that mimic gastric digestion in vivo, involving the use of pepsin uniquely or in combination with the supplement to test for additive effects. The detection of diverse cleavage sites in the caricain supplement-treated samples suggests the presence of several proteolytic enzymes that act synergistically. Caricain showed rapid action in vitro against known immunogenic ATIs, indicating its utility for digestion of wheat ATIs in the upper digestive tract.